PERAN PENGENDALIAN DIRI PERSPEKTIF FILSAFAT STOICISME TERHADAP TOLERANSI PADA MAHASISWA UIN RADEN FATAH PALEMBANG - M. Diennur; Azwar, Alfi Julizun; Jamhari, Jamhari (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2025)
This study discusses the role of self-control from the perspective of Stoicism Philosophy on tolerance in students of the Islamic Aqidah and Philosophy study program at UIN Raden Fatah Palembang, especially students of 2021. The purpose of this study is to determine the urgency of self-control in realizing tolerance, the role of self-control and self-control efforts in realizing tolerance and forms of tolerance in self-control in students of the Islamic Aqidah and Philosophy study program at UIN Raden Fatah Palembang. This type of research is field research with researchers directly going into the field supported by primary and secondary data sources. The analysis technique used is the results of interviews that are described and then concluded. The conclusion of this study is the urgency of self-control in realizing tolerance by understanding the nature of existence as a social being. In addition, the role of self-control is very vital because it is used to minimize unwanted things. Efforts to control oneself to realize tolerance always reflect on oneself and are ready to mingle in every situation. The form of tolerance from self-control of students of the Islamic Aqidah and Philosophy study program at UIN Raden Fatah Palembang is being able to accept and be open. This is analyzed through the theory of Stoicism Philosophy which teaches Living in Harmony with Nature, Dichotomy of Control, and Being Able to Control Perception and Interpretation.